Science and religion : new historical perspectives - Dixon, Thomas (Thomas M.); Cantor, G. N., 1943-; Pumfrey, Stephen (Cambridge : Cambridge University Press, 2010)
'The idea of an inevitable conflict between science and religion was decisively challenged by John Hedley Brooke in his classic Science and Religion: Some Historical Perspectives (Cambridge, 1991). Almost two decades on, Science and Religion: New Historical Perspectives revisits this argument and asks how historians can now impose order on the complex and contingent histories of religious engagements with science. Bringing together leading scholars, this new volume explores the history and changing meanings of the categories'science' and'religion'; the role of publishing and education in forging and spreading ideas; the connection between knowledge, power and intellectual imperialism; and the reasons for the confrontation between evolution and creationism among American Christians and in the Islamic world. A major contribution to the historiography of science and religion, this book makes the most recent scholarship on this much misunderstood debate widely accessible'--Provided by publisher.
Introduction / Thomas Dixon -- Pt. I. Categories.'Science' and'religion' : constructing the boundaries / Peter Harrison -- Science and religion in postmodern perspective : the case of Bruno Latour / Jan Golinski -- Pt. II. Narratives. Religion and the changing historiography of the scientific revolution / Margaret J. Osler -- The late Victorian conflict of science and religion as an event in nineteenth-century intellectual and cultural history / Frank M. Turner -- Islam, Christianity, and the conflict thesis / B. Harun Kucuk -- Pt. III. Evolution and creationism. Evolution and creationism in the Islamic world / Salman Hameed -- Understanding creationism and evolution in America and Europe / Bronislaw Szerszynski -- Pt. IV. The politics of publishing. A global history of science and religion / Sujit Sivasundaram -- The Scopes trial beyond science and religion / Adam R. Shapiro -- Science, religion, and the history of the book / Jonathan R. Topham -- Pt. V. Ways forward. Sciences and religions : what it means to take historical perspectives seriously / Noah Efron -- Simplifying complexity : patterns in the history of science and religion / Ronald L. Numbers -- What shall we do with the'conflict thesis'? / Geoffrey Cantor.
Includes bibliographical references (p. 299-310) and index.
Keywords: Religion and science -- History